Moral Philosophy on the Threshold of Modernity
VI, 344 p.
Keywords: This volume investigates the paradigm changes which occurred in ethics during the early modern era (1350-1600). While many general claims have been made regarding the nature of moral philosophy in the period of transition from medieval to modern thought, the rich variety of extant texts has seldom been studied and discussed in detail. The present collection attempts to do this. It provides new research on ethics in the context of Late Scholasticism, Neo-Scholasticism, Renaissance Humanism and the Reformation. It traces the fate of Aristotelianism and of Stoicism, explores specific topics such as probabilism and casuistry, and highlights the connections between Protestant theology and early modern ethics. The book also examines how the origins of human rights, as well as different views of moral agency, the will and the emotions, came into focus on the eve of modernity. Target audience: students of medieval, Renaissance and Reformation history; students of the history of philosophy, ethics and theology; those interested in humanism, human rights and the history of law.